Thermal balance and comparison of gas and dust properties of dense clumps in the Hi-GAL survey. Issue 4 (21st December 2018) - Merello, M; Molinari, S; Rygl, K L J; Evans, N J; Elia, D; Schisano, E; Traficante, A; Shirley, Y; Svoboda, B; Goldsmith, P F
ABSTRACT: We present a comparative study of physical properties derived from gas and dust emission in a sample of 1068 dense Galactic clumps. The sources are selected from the cross-match of the Herschel Infrared Galactic Plane Survey with 16 catalogues of NH3 line emission in its lowest inversion (1, 1) and (2, 2) transitions. The sample covers a large range in masses and bolometric luminosities, with surface densities above Σ = 0.1 g cm −2 and with low virial parameters α < 1. The comparison between dust and gas properties shows an overall agreement between T kin and T dust at volumetric densities n ≳ 1.2 × 10 4  cm −3, and a median fractional abundance χ(NH3 ) = 1.46 × 10 −8 . While the protostellar clumps in the sample have small differences between T kin and T dust, prestellar clumps have a median ratio T kin / T dust  = 1.24, suggesting that these sources are thermally decoupled. A correlation is found between the evolutionary tracer L / M and the parameters T kin / T dust and χ(NH3 ) in prestellar sources and protostellar clumps with L / M < 1 L⊙  M⊙ −1 . In addition, a weak correlation is found between non-thermal velocity dispersion and the L / M parameter, possibly indicating an increase of turbulence with protostellar evolution in the interior of clumps. Finally, different processes are discussed to explain the differences between gas and dust temperatures in prestellar candidates, and the origin of non-thermal motions observed in the clumps.